Airbnb and hotel revenues in popular Greek destinations. Issue 4 (19th August 2020) - Apergis, Nicholas; Hayat, Tasawar; Saeed, Tareq
Abstract : Purpose: This paper explores the role of Airbnb listings on hotel revenues in certain popular Greek tourist destinations. Design/methodology/approach: This paper explores the role of Airbnb listings on hotel revenues in certain popular Greek tourist destinations. The analysis makes use of the panel GMM method, while the findings document that the Airbnb listings exert a negative impact on hotel revenues. Findings: The results indicate that it is primarily non-business and low-price hotels that are being influenced, while the hotel industry responds to the competition through lower room prices and not through occupancy rates. The paper documents that although the Airbnb is a new factor in the Greek tourism industry, it has turned into a significant competitor against hotels. Originality/value: This is the first paper which documents that although Airbnb is a new factor in the Greek tourism industry, it has turned into a significant competitor against hotels. The findings are expected to provide further insights into the workings of the sector and the potential regulated policies needed to be adopted.